Effect of lidocaine topical anesthetic preparation on microbial growth - Bergado, Grace D.; Vergel de Dios, Nanette (Adviser).
This study intends to determine the antimicrobial activity of Xylocaine 5% topical anesthetic and Lidocaine (pure form) against Staphylococcus aureus, Enterococci, B-Hemolytic streptococcus and Candida albicans. An experiment was conducted in-vitro using the disc diffusion method. Zone of inhibition is indicative of antimicrobial property. Results showed that Xylocaine 5% and Lidocaine have no antimicrobial activity against S. aureus, Enterococci, B-Hemolytic strep. and C. albicans.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Anesthesia in dentistry; Lidocaine